The Impact of Resource Revenue on Non-Resource Tax Revenue in Oil-Exporting Countries: Evidence from Nonlinear Analysis - Slimane, Sarra Ben (International Journal of Energy Economics and Policy, 2024)
The main objective of this study was to examine the asymmetric effect of resource tax revenues on non-resource ones in oil-rich countries, as most previous research on the subject has assumed a symmetric resource-non-resource tax revenue nexus. We employed linear ARDL model to analyze the short- and long-term effects and found a negative relationship between resource and non-resource tax revenues. Based on nonlinear ARDL model estimates, empirical results provide strong evidence for the asymmetric effect of resource tax revenues. In the long-run, positive shocks have negative impacts on non-resource tax revenues. Conversely, negative shocks were found to not lead to increased non-resource tax revenues. In addition, findings show that the short-term effects are stronger when resource tax revenues increase.